ISOLASI, KARAKTERISASI, DAN IDENTIFIKASI BAKTERI Aeromonas sp. PENYEBAB PENYAKIT Motile Aeromonas Septicemia (MAS) PADA GURAMI - Mulia, Dini Siswani (Universitas Muhammadiyah Purwokerto, 2010)
These research were conducted to isolate, characterize, and identify bacterium Aeromonas sp. causative agents of Motile Aeromonas Septicemia (MAS) in gouramy. Samples of sick gouramy with MAS attack symptoms were taken random from tree regencies, i.e. Banyumas regency (Pliken and Lemberang), Purbalingga regency (Padamara and Jompo), and Banjarnegara regency (Kaliwinasu and Blimbing). Ten isolates were isolated from ren of gouramy on Glutamat Starch Phenile (GSP). Koch Postulat Test was conducted to determine pathogenic bacteria by intramuscular injection to gouramy (10-12 cm of total length) suspension bacteria 0.1 ml at 109 cell/fish, and control with 0.1 ml sterile PBS pH 7.0. Â Then, the pathogenic bacteria were identified with morphological and biochemical test. Results indicated that 10Â isolates were pathogenic bacteria and morphological and biochemical tests suggested that the pathogenic bacteria could be identified to be Aeromonas hydrophila.